The integration of edge computing into college physical education teaching reform under the guidance of hierarchical teaching theory - Guo, Ge; Sudiarta, Gusti Putu; Padmadewi, Ni Nyoman; Dharmad, Made Agus (Frontiers in Education, 2025)
With the development of information technology and the integration and application of artificial intelligence technology and education, great changes have taken place in college physical education teaching mode, which has triggered a new round of reform. In order to meet the needs of the development of physical education teaching in colleges and universities, this paper puts forward a research scheme integrating edge computing for the reform of physical education teaching in colleges and universities under the layered teaching theory, and realizes the combination of traditional teaching resources through the integration of physical education teaching resources. At present, the education industry has changed to a certain extent in all aspects. Due to the rigid teaching methods in the past, the development of PE has been affected to some extent. Therefore, this paper analyzes the PE teaching according to the layered teaching theory. The analysis results show that layered teaching can solve the problems of imbalance of teaching resources and failure to meet teaching requirements in PE teaching. After stratified teaching, students’ academic performance has been improved by 30%, and their sense of cooperation has been effectively improved. It can be seen that the layered teaching theory can play an extremely important role in PE teaching. Based on traditional ideas, this paper explores the application of edge computing in physical education teaching, which plays a certain role in promoting physical education teaching.